Construction of a BIM smart building collaborative design model combining the Internet of Things - Feng, Man; Wu, Hanmei (Nonlinear engineering, 2025)
The research aims to solve the problem of data synchronization and redundancy in building information model co-design with blockchain technology. A hyper-ledger fabric federated blockchain, combined with a revolving door compression algorithm, is used for the construction of an intelligent building co-design model. Experiments showed that the method outperformed other blockchain technologies in terms of throughput and response time, with block-out time reduced by 19.31% and transaction throughput increased by 12.38%. The research proposes an innovative cycle division mechanism and utilizes a revolving door compression algorithm for data maintenance of the model, thereby enhancing the security of the design data and the efficiency of collaboration. This is of positive significance for intelligent building design. However, the limitation of the study is that only the blockchain-based model is designed, and further development and example validation are needed in the future.